Analisa Hasil Kekasaran Permukaan Kayu terhadap Jenis Ketam - Rahman Hakim; Hanifah Widiastuti (Politeknik Negeri Batam, 2017)
A plane is a tool related to woodworking, which is used for smoothening the surface of the wood. Currently, there are many different smoothing planes available in the market. In this study, the evaluation of a self-made hand plane was conducted. One of the variables that can be utilized to investigate smoothing plane’s performance is by analyzing its wood’s surface smoothening capability. In this reserch, the smoothening capability was evaluated by measuring the wood’s surface roughness after the smoothening process. This study was conducted by utilizing three different types of wood namely limestone wood, meranti wood, and kempas wood as well as three different planes that are a mini plane (self-made tool), a commercial plane, and a power planer. The results show that prior to smoothening process, the maximum surface roughness was 16.432 µm for wet limestone wood and the minimum was 7,871 µm for kempas oven wood. After the smoothening process, the surface maximum roughness values are 10,932 µm using hand mini plane, 12,329 µm for kapur basah wood with the commercial plane for kapur basah wood and minimum roughness of 4,982 µm obtained hand mini plane for meranti oven wood and 5,826 µm for meranti oven wood with the commercial plane. It was also observed that the self-made mini plane gave lower values of surface roughness compared to commercial plane. Thus, it could be summarized that the self-made plane (mini hand plane) is capable to be used for the wood surface smoothening and it has better performance compared to the commercial plane.